Protease and Bacillus coagulans Supplementation in a Low-Protein Diet Improves Broiler Growth, Promotes Amino Acid Transport Gene Activity, Strengthens Intestinal Barriers, and Alters the Cecal Microbial Composition - Junlong Niu; Yingying Qiao; Xiaopeng Yang; Xiaoshuang Chen; Hongfei Li; Yongpeng Guo; Wei Zhang; Zhixiang Wang (Animals)
Low-protein (LPRO) diets can effectively reduce feed costs and decrease environmental pollution, making them an important pathway to enhance the sustainability of livestock production. However, they may have adverse effects on the growth performance of broiler chickens, which has limited their widespread application. This study aims to explore the impact of adding protease (PRO) to LPRO diets on the growth performance of broiler chickens, especially under conditions with or without the presence of Bacillus coagulans (BC), in order to provide theoretical support for the scientific application and promotion of LPRO feeds. We selected 432 one-day-old broiler chickens and divided them into four treatment groups, which were fed with the control (CON) diet, the LPRO diet, the PRO diet (LPRO diet with added protease), and the PAB diet (PRO diet with added BC). The LPRO group demonstrated decreased growth performance while both PRO and PAB diets resulted in a significant increase (p < 0.05). Both PRO and PAB diets significantly enhanced the expression of amino acid transport genes and tight junction genes (p < 0.05) and optimized the composition of the intestinal microbiota. Overall, LPRO diets have a detrimental effect on the growth of broiler chickens, while the PRO and PAB diets effectively counteract these negative effects by improving protein digestion, amino acid absorption, and intestinal health.